Peran Dan Fungsi Komunikasi Interpersonal Kepala Sekolah - Aswaruddin, Aswaruddin; Anggraini, Anggi; Sirait, Fauzan Azhima; Sibarani, Lola Amalia; Harahap, Tri Suci Apriani (Penerbit Widina, Widina Media Utama, 2025)
Interpersonal communication has a crucial role in building healthy relationships between individuals. Effective communication can strengthen emotional connections, improve listening skills, and prevent miscommunication and conflict. This study aims to analyse the role and function of interpersonal communication in building relationships between individuals. The method used is qualitative with a literature study, namely data collection through understanding and learning theories from relevant literature. Interpersonal communication also plays an important role in strengthening cooperation, appreciation, and support between parties. In the context of education, the communication of the principal plays a role in improving teacher discipline and responsibility through exemplary behaviour and coordination in solving learning problems. The results of the study show that interpersonal communication plays a significant role in strengthening relationships, resolving conflicts, and increasing productivity. This communication also creates a harmonious environment and strengthens personal relationships. This finding confirms that interpersonal communication is a strategic element in building meaningful connections in various aspects of life, including in the digital age.ABSTRAKKomunikasi interpersonal memiliki peran krusial dalam membangun hubungan yang sehat antar individu. Komunikasi yang efektif dapat memperkuat koneksi emosional, meningkatkan keterampilan mendengarkan, serta mencegah miskomunikasi dan konflik. Penelitian ini bertujuan untuk menganalisis peran dan fungsi komunikasi interpersonal dalam membangun hubungan antar individu. Metode yang digunakan adalah kualitatif dengan studi pustaka, yakni pengumpulan data melalui pemahaman dan pembelajaran teori-teori dari literatur yang relevan. Komunikasi interpersonal juga berperan penting dalam memperkuat kerjasama, penghargaan, dan dukungan antar pihak. Dalam konteks pendidikan, komunikasi kepala sekolah berperan dalam meningkatkan disiplin dan tanggung jawab guru melalui contoh teladan serta koordinasi dalam memecahkan masalah pembelajaran. Hasil penelitian menunjukkan bahwa komunikasi interpersonal berperan signifikan dalam mempererat hubungan, menyelesaikan konflik, dan meningkatkan produktivitas. Komunikasi ini juga menciptakan lingkungan yang harmonis dan mempererat hubungan pribadi. Temuan ini menegaskan bahwa komunikasi interpersonal adalah elemen strategis dalam membangun koneksi yang bermakna di berbagai aspek kehidupan, termasuk dalam era digital.